2021
DOI: 10.1111/ijfs.15330
|View full text |Cite
|
Sign up to set email alerts
|

Effect of co‐fermentation and sequential fermentation of Candida versatilis and Lactococcus lactis subsp. cremoris on unsalted pork hydrolysates components

Abstract: In this study, the effect of co-fermentation and sequential fermentation with a typical halophilic soy sauce yeast Candida versatilis and a non-halophilic dairy bacterium Lactococcus lactis subsp. cremoris in pork hydrolysates was explored for the first time with regard to their viability, physicochemical changes and volatile compound production. It was observed that the growth of C. versatilis was suppressed (only 0.6 -1.5 log CFU mL À1 increase), whilst L. lactis subsp. cremoris was stimulated (total cell co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…It is not only a beneficial fungus in Panxian ham [ 28 ], but also an important fungus in the fermentation and ripening of sausage [ 29 ]. Candida had the highest relative abundance in GZZY (19.53%), and it plays a vital role in the formation of meat flavor and can promote the decomposition of protein in fermented meat products [ 30 ]. Mi [ 31 ], reported that Kazachstania was one of the core fungi in sour meat.…”
Section: Resultsmentioning
confidence: 99%
“…It is not only a beneficial fungus in Panxian ham [ 28 ], but also an important fungus in the fermentation and ripening of sausage [ 29 ]. Candida had the highest relative abundance in GZZY (19.53%), and it plays a vital role in the formation of meat flavor and can promote the decomposition of protein in fermented meat products [ 30 ]. Mi [ 31 ], reported that Kazachstania was one of the core fungi in sour meat.…”
Section: Resultsmentioning
confidence: 99%